Managing for Ethical-Organizational Integrity - Palmer, Daniel E (Business Expert Press, 2012)
Ebook from IG Library ; For some time people thought that business and ethics constituted separate and mutually exclusive realms. Businesses that perpetuate such a belief or still hold that "business ethics" is an oxymoron are at risk. Indeed, managers are now being called on to actively promote ethical organizational integrity. This means understanding the principles that define and creating an organizational culture that measurably encourages ethical conduct. The reason for this shift in paradigm is clear. Ethical organizational integrity drives long-term company success and sustainable value production, serves to prevent illegal conduct, and best contributes to overall social welfare. This book provides a brief introduction to and general framework for managing for ethical-organizational integrity that will be useful to managers and business students alike.